Persepsi Siswa terhadap Keterampilan Mengajar Guru di SMK Negeri 1 Lembah Gumanti - Nola Safitri; Sulastri Sulastri; Jasrial Jasrial; Nelfia Adi (Journal of Educational Administration and Leadership, 2021)
This study is based on the results of the author's observations at SMK Negeri 1 Lembah Gumanti regarding Teacher Teaching Skills which are still not being implemented optimally. This study aims to obtain information about Student Perceptions of Teacher Teaching Skills at SMK Negeri 1 Lembah Gumanti from the indicators of opening lessons, explaining, asking questions, providing reinforcement, class management, and closing lessons. This study is descriptive with quantitative methods. The population of this study were 515 students of SMK Negeri 1 Lembah Gumanti class XI and XII in the Department of Communication, Hospitality, Culinary, Clothing, so the sample size was 89 respondents. Sampling in this study used the Stratified Propotional Random Sampling technique. The materials collected using a questionnaire with a Likert scale have been tested for validity and reliability. The average formula is used in processing the data in this study. The data show student responses regarding the skills of teachers from: (1) opening good category lessons with a value of 3.84; (2) describes the good category with a value of 3.84; (3) asking for a fairly good category with a score of 3.52; (4) provides a fairly good category reinforcement with a score of 3.46; (5) managing good category classes with a score of 3.73; (6) closing the lesson in the category of good enough with a score of 3.57. Overall Students' Perceptions of Teacher Teaching Skills at SMK Negeri 1 Lembah Gumanti were in a good category with a score of 3.66.